2001
DOI: 10.1161/hc4201.099224
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Distal-Balloon Protection System on Microembolization During Carotid Stenting

Abstract: Background-The distal-balloon protection system is being evaluated for its efficacy in preventing embolic neurological events during carotid stenting (CAS). We sought to determine the effect of this system on the frequency of Doppler-detected microembolic signals (MES) during CAS. Methods and Results-Using transcranial Doppler, we compared the frequency of MES during CAS in 2 groups: 39 patients without distal protection and 37 who used the distal-balloon protection system (GuardWire). There were no significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
140
2
8

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(156 citation statements)
references
References 17 publications
6
140
2
8
Order By: Relevance
“…The potential for distal embolization of plaque fragments to the brain during CA stent placement spurred the development of a variety of distal embolization protection devices. 13 The deployment of a stent in addition to angioplasty increases the occurrence of microembolic events as detected by transcranial Doppler sonography, 1 potentially increasing the risk of thromboembolic complications. A systematic review in 2003 found that DPD appeared to reduce the number of thromboembolic complications of CA stent placement, 10 a view that was confirmed by a review that incorporates the results of several trials that have been completed since.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for distal embolization of plaque fragments to the brain during CA stent placement spurred the development of a variety of distal embolization protection devices. 13 The deployment of a stent in addition to angioplasty increases the occurrence of microembolic events as detected by transcranial Doppler sonography, 1 potentially increasing the risk of thromboembolic complications. A systematic review in 2003 found that DPD appeared to reduce the number of thromboembolic complications of CA stent placement, 10 a view that was confirmed by a review that incorporates the results of several trials that have been completed since.…”
Section: Discussionmentioning
confidence: 99%
“…1,[17][18][19] Because of this relatively high incidence of adverse effects, efforts have been made to reduce their incidence by using CPDs during CAS. 4,5,20,21 An extensive literature review indicates that the use of CPD can decrease the incidence of 30-day combined stroke and death rate after CAS from 5.5% without the use of CPD to 1.8% with CPD. 4 Wholey et al, 22 on the global carotid artery stent registry, reported a reduction in stroke rate and procedure-related death from 5.29% in patients without protection to a 2.23% rate when using protection.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale behind this objective was based on the observations of several authors. 20,27 Al-Mubarak et al 20 demonstrated by TCD that the embolic events are related to the endovascular manipulations. Men et al 27 stated that less catheter and guidewire manipulations and the elimination of balloon dilation before and after stent deployment should result in a decreased number of Doppler-detected microembolic signals (MES) during the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…34 Therefore, it is very important to reduce the maneuvers as much as possible. Less manipulation with the guidewire or the catheter and the minimizing of balloon dilation reduces the number of emboli detected on transcranial Doppler.…”
Section: Figmentioning
confidence: 99%